Copper complex molecules as dye-sensitizers: Hybrid MetaGGA and standard + van der Waals functionals - Camacho Montes, Hector (2024)
This study focuses on the use of Density Functional Theory calculations with two main approaches: computational chemistry and computational physics. The following three cases were considered for the derivation: (I) computational chemistry using the M06 hybrid functional, (II) computational chemistry using the standard PBE functional including vdW interactions, and (III) computational physics using the standard PBE functional including vdW interactions and periodic boundary conditions.